The Indigenous Politics of Justice: the Case of the Sedulur Sikep Movement in Central Java - Ronald Adam; Zainal Abidin Bagir (Universitas Gadjah Mada, 2022)
The struggle by indigenous people to protect their land from capitalist expansion is often reduced by scholars to two contrasting models: class politics and identity politics. This reduction has partially come from how scholars separate between the cultural/spiritual and the political-economic dimensions of these struggles, which are often more complex in reality. Based on an empirical study of the Sedulur Sikep movement in Pati, Central Java, the purpose of this article is to understand what the indigenous politics of justice looks like in practice as they defend their land and way of life against the cement mining industry. This study uses a qualitative approach combining four months of field observations with two Wong Sikep households and interviews with 20 Wong Sikep individuals from 15 households in Baturejo Sukolilo Village, Pati Regency, Central Java. This article discusses two findings from the study. First, the cultural/spiritual and political-economic dimensions are inseparable in the lives of Wong Sikep. Such inseparability is manifested through the agricultural system as the core of Wong Sikep life, derived from the teachings of their ancestors (culture/spirituality) as well as their practical needs (political economy). Second, this inseparability forms the basis of their adoption of both the politics of recognition and redistribution in their resistance to cement mining. The article concludes with recommendations for future studies about the Sedulur Sikep movement in particular and for indigenous justice movements more broadly.